ความคิดเห็นต่อการเลือกสถานพยาบาลตามโครงการนำร่องเลือกสถานพยาบาลด้วยตนเองของประชาชน เขตประเวศ กรุงเทพมหานคร ภายใต้นโยบายหลักประกันสุขภาพถ้วนหน้า - ธนพร สุดยอดสุข (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
The objective of this study was to evaluate the opinion and perception of population in Pravet District regarding self selection of Health Service Unit on Pilot Project under the Universal Coverage Health Insurance. The study was a cross-sectional descriptive study conducted during December 2003 February 2004 by self administered questionnaires of 545 representative people from target group of 794 household samples (response rate 72.4 %). The study revealed that the most respondents were male (52.4%), average age 42 years old. The education level was primary school (47.7%). Occupation was a general worker (67.4%) and adequate earning (58.8%). The almost respondents have right to access the health service under the Universal Coverage Health Insurance card (30 bath) (93.9%). The nearest and most convenient transport to health care unit for them is the government hospital (32.7%). When self selection of Health Service Unit on Pilot Project under the Universal Coverage Health Insurance project started, it was observed that the people did not get any information (41.0%) and did not know right to select the health service unit (61.4%). However, they know how to select the health service unit in which chosen by their district, the primary health service unit, and the secondary health service units, (70.4%, 74.2%, and 66.1% respectively). Most people agree with the right to select health service units, primary and secondary health service units and standard health service units for someone{174}s desire (89.6%, 90.0%, and 82.6 % respectively). Moreover, a reason to select that unit is satisfying in service (46.2%). The study indicated that more than fifty percent did not know the right to select health service unit, but more than fifty percent agreed with Self Selection Health Service Unit on Pilot Project. So the study reflects the defect of Information Quality that is result- based indicator in monitoring and evaluation for future health services development.